XPS studies of radiation grafted PTFE-g-polystyrene sulfonic acid membranes - Nasef, Mohamed Mahmoud; Saidi, Hamdani; Mohd. Nor, Hussin; Yarmo, Mohd. Ambar (John Wiley & Sons, 2000)
Structural investigations of PTFE-g-polystyrene sulfonic acid membranes prepared by radiation grafting of styrene onto PTFE were conducted by X-ray photoelectron spectroscopy (XPS). The analyzed materials included original PTFE film as a reference material, grafted film, and sulfonated membrane samples having various degrees of grafting. Interest is focused on C1s, F1s, O1s, and S2p of narrow XPS spectra as the basic elemental components of the membrane. The original PTFE film was found to undergo structural changes in terms of chemical composition and shifting in binding energy induced by incorporation of sulfonated polystyrene grafts, and the amount of such changes depends on the degree of grafting. The atomic ratio of F/C was found to decrease with the increase in the degree of grafting, while that for S/C and O/C were found to increase.